2007
DOI: 10.1007/s10682-006-9140-x
|View full text |Cite
|
Sign up to set email alerts
|

Out of the frying pan into the fire: an ecological perspective on evolutionary reversal in life history in plethodontid salamanders (Amphibia: Plethodontidae)

Abstract: I review and analyze interaction webs involving competition and predation in ensembles of plethodontid salamanders in the southern Appalachian Mountains, USA. The objective is to evaluate hypotheses on interaction webs and population regulation in these ensembles in the context of traditional and recent models of phylogeny and life-history evolution of plethodontids. Two ecological hypotheses evaluated are (1) Hairston's conjecture on differences in the kinds of interactions prevalent among biphasic species wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Phaeognathus, the sister taxon of Desmognathus, displays direct development, as do sequential outgroups to the desmognathines. Furthermore, spelerpines (most having stream larvae) are deeply nested, raising the possibility that stream larvae, so long associated with plethodontid origins (Bruce, 2005(Bruce, , 2007, might have been independently derived in desmognathines and spelerpines. In the first major clade, the plethodontines, parsimony argues in favor of an ancestral condition of direct development.…”
Section: History Of the Plethodontidaementioning
confidence: 99%
See 1 more Smart Citation
“…Phaeognathus, the sister taxon of Desmognathus, displays direct development, as do sequential outgroups to the desmognathines. Furthermore, spelerpines (most having stream larvae) are deeply nested, raising the possibility that stream larvae, so long associated with plethodontid origins (Bruce, 2005(Bruce, , 2007, might have been independently derived in desmognathines and spelerpines. In the first major clade, the plethodontines, parsimony argues in favor of an ancestral condition of direct development.…”
Section: History Of the Plethodontidaementioning
confidence: 99%
“…They proposed a new taxonomy with four subfamilies: Bolitoglossinae (which included the former Bolitoglossini minus Hydromantes, a taxon not included in their analysis but from results of Mueller et al, 2004, by implication placed in their Plethodontinae), Hemidactyliinae (for Hemidactylium only), Plethodontinae (which included the former Plethodontini plus Desmognathinae), and Spelerpinae (the former Hemidactyliini minus Hemidactylium). This taxonomy was widely adopted (e.g., Bruce, 2007;Frost, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2; see also Hairston 1949; Burton and Likens 1975; Petranka et al 1993, 1994; Harper and Guynn 1999; Smith and Petranka 2000; Petranka and Murray 2001; Ford et al 2002; Wilson and Dorcas 2003). Although there are some microhabitat differences between species within and between clades, species from these three clades occur microsympatrically in springs, seepages, streams, and adjacent forested habitats in ENA (e.g., Petranka and Smith 2005), and some of the larger, predatory species are even known to feed on species in other clades (reviewed in Bruce 2007).…”
mentioning
confidence: 99%
“…Camp et al (2007) argued that the long-continued uplift of the southern Appalachians during the late Cenozoic provided new habitats to be exploited by the contemporaneously radiating desmognathines. They downgraded the role of interclade competition, disagreeing with Chippindale et al (2004) who suggested that competition avoidance with terrestrial salamanders may have been a major factor promoting re-evolution of larvae and occupation of diverse aquatic habitats (see also Bruce 2007).…”
Section: How Did Karsenia End Up In Korea?mentioning
confidence: 99%